Digitization and health inequality and equity in nursing: A scoping review. - Hochmuth, Alexander; Wrona, Kamil J.; Exner, Anne-Kathrin; Dockweiler, Christoph (Pflege, 2021)
Background: The use of information and communication technologies (ICT) in health care is increasing attention. To describe health inequalities and equity with regard to the use of digital health technologies in a care context and to understand interrelationships, it is of particular importance for the field of care research to use models and theories that explain health inequalities and equity in the use of digital technologies. Aims: This article aims to identify models and theories from the field of nursing and health research that explain the phenomenon of health inequalities and the influence of digital health technologies on the emergence of inequalities. Methods: Relevant articles were searched in electronic databases (MEDLINE, CINAHL & SocINDEX) between July and August 2019 in German and English, within the methodological framework of a scoping review. The systematic literature search and data extraction were performed by 2 reviewers. The description of data refers to standard criteria by 8-1Christiansen and Baum (1997). Results: From a total of 25 relevant articles, 2 were identified for inclusion in the current overview. One model is focusing on ICT for health and the other model focuses on eHealth. No nursing theory could be identified in the context of describing the phenomenon of digital inequality. Conclusions: In both models, there is a lack of discussion about the impact of nursing aspects on the use and acceptance of eHealth technologies. One point should also be the development of models and theories that consider the user perspective of vulnerable groups.